Agroecology and Climate Change Resilience: In Smallholder Coffee Agroecosystems of Central America - Morris KS; Méndez, V.E.; Zonneveld, M. van; Gerlicz A; Caswell, M. (Bioversity International, 2016)
Arabica coffee production provides the principal source of monetary income for many smallholder households throughout the mountainous regions of Central America. Coffee agroecosystems serve several functions, which can include supporting livelihoods, and providing ecosystem services (e.g. carbon sequestration), and conserving biodiversity (De Beenhouwer et al., 2013; Valencia et al., 2014). For these reasons, coffee farming plays a key synergistic role in socioeconomic and ecological resilience. Despite these synergies, the livelihoods of Central American smallholder coffee farmers are in a precarious state due to their exposure and sensitivity to common stressors and shocks, including the seasonality of incomes, volatile commodity prices and natural disasters (Jha et al., 2014). This vulnerability makes it extremely difficult for growers to maintain (let alone build) their assets and capabilities, and to embark on pathways out of poverty.